Problematika Pengelolaan Pendapatan Asli Daerah di Era Otonomi Daerah - Lukman Santoso (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2013)
The post-reform era of regional autonomy, has brought major changes in the state system. Included in the financial management system and mechanism of local government. In the context of autonomy, in addition to the transfer of central, local governments are required to have their own sources of funding in the form of local revenue (PAD), lending area, as well as other legitimate reception area. However, in practice, in the majority of the transfer region of the Central Government is the main source of local government funding to finance daily operations, which by the local government "reported" in the budget calculations. Being the ability of the region to explore the potential of the region as revenue in the implementation of socio-economic development is still very limited. As a result, local government revenue sources are very dependent on transfers from the central government.PAD is a pure reception area and its role is an indicator of the extent of the autonomy has been widely implemented, real, and responsible. By extracting maximum revenue and the expected increase in local government is also able to improve its ability in the administration of local affairs. PAD sources determined by Law no. 22 jo 25 of 1999 and Law no. 32 jo 33 of 2004, local taxes, levies, local owned company results and other legitimate source revenues. Additionally PAD is the backbone of regional funding, therefore the ability to implement autonomy in the measure of the magnitude of the contribution made by the PAD to the total budget, so that local autonomy can be realized with either.